Efficient Ternary Organic Photovoltaic Films for Fast Exciton Separation to Generate Free Radicals for Wastewater Treatment - Linji Yang; Ciyuan Huang; Yang Zhou; Libin Zhang; Ke Sun; Houjin Luo; Yinna Liang; Yilin Wang; Tao Yang; Wei Ma; Donglou Ren; Cong Liu; et al. (Exploration)
ABSTRACT Given the effectiveness of organic pollutants photodegradation and the excellent photovoltaic nature of organic solar cells (OSCs), this work first innovatively integrated the cross‐fields of OSCs and environmental photocatalysis. Using knowledge of OSC morphology, an insertion strategy involved adding a suitable quantity of guest acceptor (Y6‐O) to the PM6 donor polymer and BTP‐2F‐ThCl host small molecule acceptor system. Y6‐O leads to tighter π–π packing, reduced domain size, and improved domain purity, resulting in favorable morphology for charge generation and transfer in devices and an improved power conversion efficiency (PCE) from 17.1% to 18.1%. Moreover, terpolymer organic photovoltaic films were applied to wastewater treatment, gaining ions Sb(III) and Sb(V) removals of 100% in 15 min, and guaiacol photodegradations of 90% in 1 h. This work significantly prompts the development of organic photovoltaics and wastewater treatment and opens views for multifunctional organic photovoltaic material applications.